Technical-economic evaluation of ground source heat pump for office buildings in China. (October 2018) - Lei, Yong; Tan, Hongwei; Li, Yue
Abstract: The adoption of ground-source heat pump (GSHP) in building sector for space heating / cooling, has increased rapidly during the past several decades around the world, especially in China. Meanwhile, it also exposed a lot of problems such as poor economic and energy efficiency, and even failure to operate properly. The purpose of this paper is to post-assess the application of existing GSHP projects, and to analyze the feasibility of ground-coupled heat pumps (GCHP) applied to office buildings in different climatic zones in China. More than one hundred GSHP cases are investigated through literature surveys and field data collection. Based on the post-evaluation results, a model for assessing the adaptability of GCHP is established. The feasibility evaluation of GCHP applied to office buildings are carried out, and key indicators, such as available capacity, energy savings, and cost-efficiency, etc. are presented among different climatic zones in China.